Pembelajaran Lintas Budaya dalam Pengembangan Kurikulum PAUD: Sintesis Praktik Terbaik Malaysia, Finlandia, Amerika Serikat, Jepang, dan Australia untuk Konteks Indonesia - Juriah, Icah; Sinambela, Esra Theresia; Harefa, Syifaushudur; Yus, Anita (Universitas Negeri Medan, 2026)
Early Childhood Education (ECE) serves as a crucial foundation in shaping children's character and potential before entering formal education. Each country develops unique ECE curricula tailored to cultural values, educational philosophy, and societal needs. This research aims to analyze and compare ECE curriculum models in five countries Malaysia, Finland, the United States, Japan, and Australia to identify best practices adaptable to the Indonesian context. The method employed is a comparative literature study analyzing curriculum documents, educational policies, and recent research findings. The analysis reveals that Malaysia implements a standardized curriculum with holistic focus, Finland emphasizes phenomenon-based learning and child well-being, the United States prioritizes individual exploration through Creative Curriculum, Japan focuses on moral character formation, while Australia develops an inclusive approach through the Early Years Learning Framework. Despite different approaches, all countries share commonalities in positioning play as the primary learning medium and teachers as facilitators. This research recommends that Indonesia integrate local wisdom values with global innovation, grant greater autonomy to teachers, and develop inclusive learning environments that respect children's cultural diversity.